2016
DOI: 10.1515/cclm-2015-0958
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary probe of quality indicators and quality specification in total testing process in 5753 laboratories in China

Abstract: Improvements are needed in all phases of total testing process (TTP) in laboratories in China, especially in examination phase. More attention should be paid when microbiology specimens are collected and results are reported. Quality specifications can provide directions for laboratories to make effort for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
6
0
5
Order By: Relevance
“…Those that did not have LIS or HIS collected related data by accessing to related records manually. Laboratory leaders or quality managers were asked to upload related data via online EQA platform for critical value reporting investigation developed by the NCCL within 2 month after receiving it voluntarily ( 6 , 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those that did not have LIS or HIS collected related data by accessing to related records manually. Laboratory leaders or quality managers were asked to upload related data via online EQA platform for critical value reporting investigation developed by the NCCL within 2 month after receiving it voluntarily ( 6 , 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is obviously inappropriate to use recommendation of one hour without verification. Besides, quality specifications can be set based on the “state-of-the-art” ( 6 ). Based on a College of American Pathologists (CAP) Q-Probes study, a laboratory goal of reporting critical results within 15 to 30 minutes after testing is complete were proposed for inpatient settings ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 Other programs on QIs have been organized and implemented in several countries. [8][9][10][11] Currently, the usual external quality assessment (EQA) scheme focuses mainly on the analytical phase of laboratory work. In this study, we designed a pre-analytical EQA scheme to evaluate pre-analytical errors on specimen collection, which included in six QIs:…”
Section: Introductionmentioning
confidence: 99%
“…Fei et al [2] reported on a major study of quality indicators covering all phases of laboratory work. The study assessed performance for over 5000 laboratories in China against 15 quality indicators, broken down by laboratory discipline where appropriate.…”
mentioning
confidence: 99%
“…It is also important to place these activities in the spectrum of basic research and original concepts, translational research and clinical application. The papers on current laboratory performance [2,3] reflect practical applications, the opinion papers on approaches to error and uncertainty [4,5] reflect background developments and discussion and the last of these papers introduces a new concept, which will need further analysis and discussion before being considered for use in setting performance specifications in the routine laboratory.…”
mentioning
confidence: 99%